Chinese-Gulf Relations Within The Framework Of The Belt And Road Initiative (Journal of Hama University, 2026)
This study sheds light on Sino-Gulf relations within the framework of the Belt and Road Initiative by analyzing the Chinese and Gulf motives for cooperation within the initiative, evaluating joint projects and their economic and geopolitical impact, and anticipating the future of these relations in light of regional and international challenges.The descriptive analytical approach was used. The researcher also relied on secondary data published in scientific and academic studies and research, reports issued by international institutions, and scientific research in this field.The researcher aimed to achieve a set of objectives, the most important of which were:Analyzing the Chinese and Gulf motives for cooperation within the initiative, and evaluating joint projects and their economic and geopolitical impact.The study reached a number of conclusions, the most important of which are:Chinese foreign policy towards the Gulf Cooperation Council (GCC) countries will remain governed primarily by economic and commercial considerations, given the importance of the GCC countries from both a geographical and economic perspective.
Keywords: Belt and Road Initiative, China-Gulf relations.